Effect of l-cysteine and l-ascorbic acid addition on properties of meat analogues. (January 2023) - Taghian Dinani, Somayeh; van der Harst, Jeroen Philip; Boom, Remko; van der Goot, Atze Jan
Abstract: Currently, studies are underway to use pea protein isolate (PPI) for the production of meat analogues because it is considered as a more sustainable alternative to soy. The potential of PPI has been demonstrated in extrusion and PPI in combination with wheat gluten has been studied in the shear cell. To enlarge the possibilities to make meat analogues with a broader range of properties, the effects of l -cysteine (CYS) and l -ascorbic acid (AA) on PPI and wheat gluten (WG) blends were examined at different concentrations (0, 100, 500, 1000 and 2000 ppm). The results showed that both CYS and AA altered the properties of the products formed by the high-temperature shear cell (HTSC). Both additives altered the fibrousness and the mechanical properties of the products obtained after processing. Especially CYS revealed an increase in tensile stress, tensile strain and Young's modulus as its concentration increased. However, products containing CYS depicted a relatively stable anisotropic index of 1, which corresponded to a densely packed matrix that was observed by microstructural analysis. A small elevated anisotropic index (>1) of products containing AA at concentrations of 500–2000 ppm could be attributed to the formation of pores parallel to the shear flow direction in these samples visualized by a confocal laser scanning microscope (CLSM) and the scanning electron microscope (SEM). In the products containing 2000 ppm of AA and 2000 ppm CYS, small and large fibers were formed, respectively. Therefore, this research pointed out the potential application of CYS and AA to alter and control the textural attributes of products. This application could aid in improving the consumer acceptance of meat analogues and, thus, contribute to being able to feed the increasing population of the world. Graphical abstract: Image 1 Highlights: l -cysteine and l -ascorbic acid were examined for the production of meat analogue. They altered properties of products formed by high-temperature shear cell. l -cysteine increased tensile stress, tensile strain and Young's modulus of products. l -ascorbic acid increased the browning index, fiber formation and anisotropy index.